Identifikasi Limbah pada Proses Produksi Obat Nyamuk Bakar dengan Menggunakan Material Balance - Sitepu, Muhamad Haikal; Andayani, Ulfa; Alda, Tania (Jurnal Sistem Teknik Industri, 2020)
Based on the initial discussion with people form Mosquito coil factory, there is a requirement to calculate the amount of waste from the factory. According to them, several wastes (in the form of liquid and solid waste) are produced in the process of making mosquito coils. The wastes are often scattered on the floor, causing the condition of the factory space to be unclean or dirty and can cause employees to get sick due to waste scattered on the floor. This research focuses on identifying the waste and to calculate the waste produced by each machine for the production of mosquito coils by using the Material Balance method. Material balance shows a quantitative analysis of material inputs, outputs and wastes / waste at each stage of the production process. Material balance calculation is done in the process of Sifting Coconut Shell Flour, Sifting Process for Coffee Skin Flour, Process for Sifting Wood Flour, Sifting Flour Sifting Process, Onggok Flour Cooking Process, Mixing Material into Mosquito Coe Dough, Mosquito Dough Sifting Process, Forming Process of Paste Paste Plate , The Process of Printing Paste Slabs Into Wet Double Coil, Drying Double Wet Coil Process, Drying and Separation Process of Baking Sheet with Dry Double Coil, Grinding Process of Broken Dry Double Coil, Process of Sifting Sweep Flour Falling on the Floor. Based on the observation, some of the waste obtained from each stage of the production process can be collected again and can be used again as a raw material for making mosquito coils.